The aspects of tradition and modernity in Chaim Potok’s novel, in The Chosen - Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
Tradition and modernity are two expressions living together and living in conflict with each other, as well. Every human being has to face the choice between these elements because people are born into a world full of traditions of their families, however, they live in communities confronting new challenges. Next to real life, the topic of the duel between tradition and modernity appears in literature, too. I introduce Chaim Potok’s novel, The Chosen from the point of view of the main characters’ struggle. Danny and Reuven live in Jewish families according to strict rules, and they watch the outside universe with curious eyes hoping that both of them are able to stand the proof.